Formulasi Dan Uji Aktivitas Sediaan Krim Fraksi Etanol Bunga Pepaya (Carica Papaya L.) Terhadap Bakteri Staphylococcus Aureus Penyebab Jerawat - Widodo, Subur; Rokiban, Akhmad; Susanti, Laila; Riyanti, Deski (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2023)
Papaya flowers in the community are believed to be antidiabetics, prevent cancer, lower cholesterol, and as antibacterial. Based on its antibacterial properties, the ethanol fraction of papaya flowers will be made in the form of cream preparations. This study aims to find out the activity of papaya flower ethanol fraction cream preparations against the bland growth power of acne-causing Staphylococcus aureus bacteria. Ethanol fractions of papaya flower are formulated into cream preparations with fraction concentrations of F1 (2%), F2 (4%), F3 (6%), and F4 (8%) using oil phases (stearic acid, paraffin liquidum, and adeps lanae), water phase (TEA and aquadest) and preservatives (methyl parabens). Furthermore, the cream tested antibacterial activity and physical properties include homogeneity, organoleptic, pH, viscosity, scattering power, adocity and stability. The results showed F1, F2, F3, and F4 each had antibacterial activity against Staphylococcus aureus bacteria as evidenced by the presence of bland zones in F1 (17.35 mm), F2 (17.77 mm), F3 (18.90 mm), and F4 (19.73 mm). The resulting data is normal and homogeneous distributed data so that the results of the ANOVA test show a significant difference of 0.0000 (p ≤ 0.05) and Tukey Post Hoc test results are obtained significant differences between formulas. The results of the evaluation of cream preparations on observation of homogeneity are less stable and organoleptic have stable results, pH values of 5.62-6.62, viscosity of 4122-4432 cps, scatter power of 5.13-5.70 cm, and akat for 4.86-6.43 seconds. Cycling tests showed stable results in F1, F2 and F3 and less stable in F4. The conclusion of this research is that the formulation ethanol fraction of papaya flower cream preparations has activity against the inhibition of the growth of acne-causing Staphylococcus aureus bacteria. Keywords: Acne, Antibacterial, Carica papaya, Cream, Fraction, Papaya Flower